Community Private Pharmacy in Costa Rica - Pereira Céspedes, Alfonso (2018)
The private sector is composed of a wide range of services, with different levels of complexity, from ambulatory to hospital care. These services are financed through private insurances and out of pocket (5). Community pharmacies are part of this sector and supplies with services to almost all of the country. By 2018, there were an estimatedmore than 1000 community private pharmacies, distributed mainly in urban areas (6). According to current regulations, there are no restrictions for the opening of a new establishment related to the distance between establishments or population covered. So, it is possible to open a pharmacy if it complies with all the legal and technical requirements (7).